Adaptation and validation of the Caregiver Burden Inventory for use with caregivers of elderly individuals - Daiany Borghetti Valer; Marinês Aires; Fernanda Lais Fengler; Lisiane Manganelli Girardi Paskulin (Universidade de São Paulo, 2015)
OBJECTIVE: to adapt and validate the Caregiver Burden Inventory for use with caregivers of older adults in Brazil.METHOD: methodological study involving initial translation, synthesis of translations, back translation, expert committee review, pre-testing, submission of the final version to the original authors, and assessment of the inventory's psychometric properties. The inventory assesses five dimensions of caregiver burden: time-dependence, developmental, physical, social and emotional dimensions.RESULTS: a total of 120 family caregivers took part in the study. All care-receivers were older adults dependent on assistance to perform activities of daily living, and lived in the central region of the city of Porto Alegre, RS, Brasil. Cronbach's alpha value for the inventory was 0.936, and the Pearson correlation coefficient for the relationship between the scores obtained on the Caregiver Burden Inventory and the Burden Interview was 0.814. The intraclass correlation coefficient was 0.941, and the value of Student's T-test comparing test and retest scores was 0.792.CONCLUSION: the instrument presented adequate reliability and the suitability of its items and factors was confirmed in this study.